عہدرسالت میں غیر مسلموں کی خدمات سے استفادہ:تاریخی جائزہ : Utilization of Non-Muslims’ Services During the Prophetic Era: A Historical Analysis - Abdul Rahim Asad,; Dr Muhammad Riaz Mahmood, (Al Manhal Research Journal, 2025)
This study explores the historical reality that the Holy Prophet Muhammad ﷺ did not restrict cooperation to Muslims alone but, whenever needed, benefitted from the knowledge, expertise and support of non-Muslims in various fields of life. Eleven personalities have been examined in this research, reflecting different stages of the Holy Prophet’s ﷺ mission. Before the Hijrah, individuals such as Waraqah ibn Nawfal, the Negus of Abyssinia, Abu Talib, Hisham ibn ʿAmr, Zuhayr ibn Umayyah, Abu al-Bukhturi, and Mutʿim ibn ʿAdi provided intellectual, political and social support to the Holy Prophet ﷺ and his followers. During and after the Hijrah, figures such as ʿAbdullah ibn Uraiqit, who acted as a guide, the captives of Badr who taught literacy, and al-Harith ibn Kaladah, a renowned physician, played key roles. Additionally, the tribe of Khuzaʿah including both Muslims and polytheists proved to be reliable allies and informants in matters of strategy and security.The findings reveal that the Holy Prophet ﷺ valued qualities such as trustworthiness, honesty, skill and professional competence above religious affiliation when engaging with others. His approach underscores the universality and inclusivity of Islam and offers a timeless model for constructive interaction with people of different faiths. The practical examples drawn from the Prophetic era demonstrate that cooperation in fields such as knowledge, medicine, diplomacy, security and social justice is both permissible and praiseworthy, so long as it advances the collective welfare of the Muslim community and adheres consistently to Islamic values.